+0  
 
0
95
3
avatar

1. 

2.

3.

Guest Feb 22, 2018
Sort: 

3+0 Answers

 #1
avatar+86613 
+2

1.

Since y equals y...we can set the frst two equations equal

 

x^2  - 2x + 4   =  -2x + 4       subtract  -2x + 4 from both sides

 

x^2  =  0    ⇒    x  =  0

 

So...only one solution  at  (0, 4)

 

Here's a graph   : https://www.desmos.com/calculator/pmhadfbhr1

 

 

cool cool cool

CPhill  Feb 22, 2018
 #2
avatar+86613 
+2

Again....we can set the equations  equal

 

x^2  - 5x + 6  =  -4x + 6       add 4x, subtract 6   to / from each side

 

x^2 - x = 0     factor

 

x ( x - 1)  = 0

 

Setting each  factor to 0   and solving for x produces x = 0  or x  = 1

 

And using    -4x  +  6

 

When x  = 0 , y  = 6

When x  = 1, y = 2

 

So...the solutions are  (0,6)  and (1,2)

 

 

cool cool cool

CPhill  Feb 22, 2018
 #3
avatar+86613 
+2

x^2 + 4x  - 10  =  8x - 14

 

Subtract  8x , add 14  from / to   both sides

 

x^2 - 4x + 4  =  0       factor

 

(x - 2) ( x - 2)  =  0

 

Setting either factor to 0 and solving for x   prduces  x  = 2

 

And  using  8x  - 14.....  y  =  8(2) - 14  =  16   -  14   = 2

 

So the solution is (2,2)

 

 

cool cool cool

CPhill  Feb 22, 2018

31 Online Users

avatar
avatar
avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy